The Relationship Levels of Clinical Nurses with Anxiety Level of Nurses in The Particular Isolation Room Covid 19 Islamic Hospital Darusyifa' Surabaya - Setiyowati, Eppy; Cornelia Sugijantoro, Alviana; Anggraeni Dwi Puspita , Reny; Salamah, Umi; Iskandar, Joni (Journal of Applied Nursing and Health, 2024)
Background: At the beginning of 2020, the whole world was shocked by the phenomenon of the Corona Virus (Covid19) pandemic which caused panic everywhere. Hundreds of thousands of people were infected and thousands more died. This really creates anxiety for all humans, especially anxiety for health workers in particular. This study aims to determine the relationship between the level of clinical nurses (PK) and the anxiety level of nurses in the Special Isolation Room (RIK) COVID-19 Darussyifa' Islamic Hospital Surabaya Methods: This study uses an observational approach with a cross sectional research design. The research population is the Nurse in the Special Isolation Room (RIK) COVID-19 Darussyifa' Islamic Hospital Surabaya. The sample size of the study was all nurses in the special isolation room of the Darusyifa Islamic Hospital, Surabaya, amounting to 27 nurses. The independent variable is the level of nurses, and the dependent variable is the level of anxiety. The research instrument is a questionnaire. Data analysis used multiple linear regression test. Results: The results showed that there .are 6 levels of clinical care levels, namely Pre PK and Level 1,2,3,4,5Based on the results of the univariate analysis, it is known that the level of clinical nurses has a relationship with the level of anxiety in the COVID-19 workspace, as evidenced by the sign value obtained 0.027, which means that p <0.05, it means that there is a relationship between the level of clinical nurses and the anxiety level of nurses in the special isolation room. Conclusion: that is, there is a relationship between the level of clinical nurses with the level of anxiety. There is a need for procedures to reduce the risk of anxiety in isolation nurses.